The Mental Imagery Training to Reduce The Impact of Teenage Bullying During Semester Exams - Afni, Andi Nur; Noviekayati, IGAA (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Bullying in schools has a significant psychological impact on adolescents, including anxiety, concentration difficulties, and decreased motivation to learn. This study aimed to examine the effectiveness of mental imagery training in reducing the psychological effects of bullying among students at SMP Negeri 28 Bulukumba. The research employed a quasi-experimental design with a pretest-posttest format and no control group. The subjects were 20 ninth-grade students identified as having experienced psychological distress due to bullying. The intervention consisted of five structured mental imagery training sessions. Pretest and posttest data were analyzed using descriptive and comparative statistical methods. The results revealed a reduction in psychological symptoms after the intervention, such as increased calmness in social situations, enhanced assertive expression, and decreased emotional reactivity. Mental imagery training proved to be an effective strategy in strengthening students' emotional resilience and minimizing the impact of bullying. These findings highlight the importance of implementing both preventive and therapeutic psychological approaches within educational settings.